PENGEMBANGAN SISTEM INFORMASI PENJUALAN PRODUK TEACHING FACTORY (TEFA) BERBASIS WEB JURUSAN DKV DI SMK NEGERI 1 KINALI - Nabil Makarim, Muhamad; Mulyono, Heri; Trisetyowati Untari, Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information technology has brought significant changes to data and transaction management in the education sector, including at the Teaching factory (TEFA) of the Visual Communication Design (DKV) Department of SMKN 1 Kinali, which produces various creative services and products for the community. Previously, sales and order data were managed manually, resulting in delayed information, recording errors, and inefficiencies in generating reports. This study aims to design and develop an integrated web-based sales information system for TEFA in order to simplify administrative processes, improve work efficiency, and support information transparency for both managers and customers. The research method applies the Software Development Life Cycle (SDLC) waterfall model, consisting of planning, analysis, design, implementation, and testing stages. User needs and system constraints were identified during the planning phase, requirements were formulated during the analysis, and system workflows were modeled using UML during the design stage. The system was implemented using PHP with the Laravel framework and a MySQL database. System testing involved black box, white box, and beta testing to ensure performance reliability. The results show that the developed system achieved an average score of 88.6% from experts and 94.3% from users, categorized as “very good,” and effectively integrates sales data, accelerates report generation, and reduces recording errors.